Effects of bladder irrigation with chlorhexidine and normal saline on prevention of bacteriuria in patient with foley catheter - Samimi, ghoncheh; Ezzati, Zhaleh; Sarokhani, Dr Mohammad Reza; Mosalaii, Dr Sasan; Mehrabi, Dr Yadollah (Advances in Nursing & Midwifery, 2011)
Effects of bladder irrigation with chlorhexidine and normal saline on prevention of bacteriuria in patient with foley catheter Samimi, Gh. 1 (MSN); Ezzati, Zh. *2 (MSN); Sarokhani, M. R.3 (PhD); Mosalaii, S. S.4 (MD); Mehrabi, Y.5 (PhD) 1. Alumnus, Faculty of Nursing and Midwifery, International Branch of Shahid Beheshti University of Medical Sciences, Tehran, Iran. 2. Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 3. Associate Professor, Dept. of Laboratory Science, Faculty of Health, Qazvin University of Medical Sciences, Qazvin, Iran. 4. Nephrologist, Bo-Ali Hospital, Qazvin University of Medical Sciences, Qazvin, Iran. 5. Professor, Dept. of Epidemiology, Faculty of Health, Shahid Beheshti University of Medical Sciences, Tehran, Iran. Abstract Background and aim Urinary tract infection (UTI) is the most common infection acquired in both hospitals and nursing homes and is usually associated with catheterization. The aim of this study was to compare the effects chlorhexidine 0.2% with saline for bladder irrigation on preventing bacteriuria in patients with foley catheter. Materials and Methods In this randomized clinical trial, 60 neurologic patients 50 years old and over in need of foley catheter for at least 14 days with no UTI at the beginning of the study were enrolled, catheterized by one of the researchers and randomly divided into two groups of chlorhexidine %0.2 and saline. Bladder irrigation was performed on days 3 and 10 following catheterization. A questionnaire and urine analysis as well as culture were used for data collection, each of which was validated and made reliable. Different statistical tests including T-student and Chi square as well as logistic regression were used for data analysis. Findings With respect to negative culture results in both groups on days 1 and 2, a significant difference was found between chlorhexidine (30%) and saline (77.3%) groups (P<0.001). All subjects contracted infection after 17 days. The relative risk for urinary tract infection in saline group was 2.4 times greater than the other group. Conclusion During the first 9 days, bladder irrigation with chlorhexidine 0.2% may lead to decreased rate of infection due to catheterization. Keywords: Nosocomial infections, Bacteriuria, Foley catheter, Bladder irrigation, Chlorhexidine 0.2% *Corresponding Author: Zhale Ezzati. Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: zh_ezzati_15@yahoo.com